POLA PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN WISATA TIRTO TANI DJOJO DI DESA TIRU LOR, KEC. GURAH, KAB. KEDIRI - A Zahid; Afra Zahrotul Ummah (Universitas Mercu Buana, 2021)
Tirto Tani Djojo Tourism is one of the new tourist destinations in the Gurah District, Kediri Regency. Basically, this tour is managed by a group called the